PENGARUH ULASAN INFLUENCER DAN DISKON DI TIKTOK DALAM KEPUTUSAN PEMBELIAN PRODUK DI TIKTOK SHOP - Aurora Shakila Ananda Syah (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2025)
This paper aims to analyze how significant the role of influencer reviews and discount offers are in influencing consumer decision to purchase products. There were 94 respondents for this study. This research uses descriptive quantitative method with Google Form as instrument. Respondents were obtained using simple random sampling technique. The results showed that influencer reviews and discounts simultaneously and partally influence purchasing decisions by consumers on the TikTok application. Through the T test (partial) influencer review variables (X1) and discounts (X2) have a significant effect on consumer purchasing decisions in the TikTok application. Then all hypotheses, H1, H2, and H3 can be accepted. This study contributes to the digital marketing literature by explaining consumer behavior in the social media era, emphasizing the importance of leveraging platforms like TikTok for effective marketing strategies.